Exploring Cardiovascular and Pulmonary Proficiency in Public Sector Physical Therapy: Insights from Kuwait's Healthcare System - Al-Mutawa, Amina (Generasi Sains Indonesia, 2024)
Cardiovascular and pulmonary diseases are significant contributors to morbidity and mortality worldwide. This study evaluates the proficiency of physical therapists in cardiovascular and pulmonary physical therapy (CPPT) within Kuwait’s public healthcare sector. A cross-sectional survey was administered to 200 physical therapists, assessing their knowledge, clinical skills, and challenges in delivering CPPT. The results revealed that 55% of therapists demonstrated moderate proficiency, with 25% exhibiting high proficiency and 20% scoring in the low proficiency category. Regression analysis identified years of experience and CPPT specialization as significant predictors of proficiency, accounting for 27% of the variance (R² = 0.27, p < 0.01). The study also highlighted key gaps in continuing professional development, with 65% of respondents identifying a need for further training in exercise prescription and 50% reporting a lack of education on rehabilitation protocols. Additionally, 40% of therapists cited insufficient specialized CPPT training programs as a major challenge, while 25% reported resource limitations. The findings underscore the need for improved training, standardized rehabilitation protocols, and enhanced resource allocation to optimize CPPT services in Kuwait. Addressing these gaps can enhance patient outcomes and improve the quality of rehabilitation services for cardiovascular and pulmonary patients in the region.